2017
DOI: 10.1186/s13071-017-2545-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical characterization of calmodulin from Echinococcus granulosus

Abstract: Background Echinococcus granulosus is a harmful cestode parasite that causes cystic echinococcosis in humans as well as various livestock species and wild animals. Calmodulin (CaM), a Ca2+ sensor protein, is widely expressed in eukaryotes and mediates a variety of cellular signaling activities.MethodsIn the present study, the cDNA encoding CaM in Echinococcus granulosus (rEgCaM) was successfully cloned and the molecular and biochemical characterizations carried out. The antigenicity and immunoreactivity of rEg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…have used Immunohistochemical localizations on different stages of the parasite, suggesting the expression of E. granulosus CaM (EgCaM) in the tegument tissues, protoscoleces parenchymal region, germinal layer as well as in the adult stage. The study showed physiologically active regions for EgCaM expression and suggested the crucial role of Ca2+ signaling pathway in the growth and development of the helminth and its function between E. granulosus and its host 9 .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…have used Immunohistochemical localizations on different stages of the parasite, suggesting the expression of E. granulosus CaM (EgCaM) in the tegument tissues, protoscoleces parenchymal region, germinal layer as well as in the adult stage. The study showed physiologically active regions for EgCaM expression and suggested the crucial role of Ca2+ signaling pathway in the growth and development of the helminth and its function between E. granulosus and its host 9 .…”
Section: Introductionmentioning
confidence: 83%
“…Wang et al . showed EgCaM expression in the germinal layer and speculated that an unknown calcium-dependent mechanism occurs in this layer 9 . More in-depth investigations are needed on the probable role of CaM in the stability of the microcyst wall and germinal layer.…”
Section: Discussionmentioning
confidence: 99%
“…Among the calmodulin-binding proteins, calcineurin has been found to be involved in apoptosis-related pathway initiation. Calmodulin was predicted as a potential drug target in E. multilocularis [54], and more recently identified and characterized in E. granulosus (Egcam) [56]. Egcam was shown to be expressed in the larva, germinal layer, and adult worm.…”
Section: Regulated Cell Death Of the Echinococcus Parasitementioning
confidence: 99%
“…The CaM gene is also expressed in the tegument tissue and parenchymal region of PSC [ 15 , 16 ]. In terms of evolution, CaM is one of the most ancient proteins in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…The functions of CaM include Ca 2+ binding and conversion of Ca 2+ signals through downstream proteins to regulate various physiological processes, such as muscle contraction, metabolism and cell motility [ 17 ]. Calcineurin and CaM have been linked to the regulation of the life cycle, development and cellular signaling activities, thus being potentially promising targets for the development of drugs that block the invasion of parasites and limit their growth [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%